Implementasi e-FAKTUR 2.2 dan PMK 62/PMK03/2015 atas Pupuk Bersubsidi Perspektif Distributor - Midiawati, Endang Sri; Herwanti, Titiek; Husnan, Lalu Hamdani (E-Jurnal Akuntansi; Vol 31 No 1 (2021), 2021)
E-fakur 2.2 is a manifestation of  Undang-undang No. 42 of 2009 concerning Value Added Tax (VAT) which does not accommodate VAT subsidies for commodity Fertilizer packages which have an impact on SAS VAT for distributors. This study aims to see how the implementation of subsidized fertilizer commodity e-invoices with the government-borne method (PPN DTP). General problems regarding the legal basis which technically only explain down to the producer level. The results of observations in a case study by processing data from 2016 onwards show problems in their implementation, both from administration, validation sistems and developing information on supervision and cross-information, especially on the management of SAS PPN through e-faktur2.2 from the distrbutor perspective. Keywords :  E-Faktur;  VAT S ubsidized; Su bsidized Fertilzer.